Shareholders at the Gate? Institutional Investors and Cross-Border Mergers and Acquisitions - Ferreira, Miguel A.; Massa, Massimo; Matos, Pedro (Review of Financial Studies, 2010)
We study the role of institutional investors in cross-border mergers and acquisitions (M&As). We find that foreign institutional ownership is positively associated with the intensity of cross-border M&A activity worldwide. Foreign institutional ownership increases the probability that a merger deal is cross-border, successful, and the bidder takes full control of the target firm. This relation is stronger in countries with weaker legal institutions and in less developed markets, suggesting some substitutability between local governance and foreign institutional investors. The results are consistent with the hypothesis that foreign institutional investors act as facilitators in the international market for corporate control; they build bridges between firms and reduce transaction costs and information asymmetry between bidder and target. We conclude that cross-border portfolio investments of institutional money managers and cross-border M&As are complements in promoting financial integration worldwide.